The Effect of Digital Marketing and Customer Relationships on MSME Performance: Pengaruh Digital Marketing dan Customer Relationship terhadap Kinerja UMKM - Nugraeni; Zaenal Wafa; Nur’aini; Regas Panji Pratomo (Journal Financial, Business and Economics, 2025)
The purpose of this study is to determine whether digital marketing and customer relationships affect the performance of MSMEs. To maintain economic stability, especially for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, MSMEs must be able to increase sales turnover, increase consumer orders, and facilitate access to raw materials. MSMEs must have a strategy to survive and are required to be able to adapt to emerging conditions. Businesses that can survive are those that are responsive to changes in their environment and are able to adapt, both in terms of products, marketing and sales systems, and the use of technology that supports the business. This study aims to determine the effect of digital marketing and customer relationships on MSME performance.